A comparative study of bilateral lsias verses conservative management in acute anal fissure - Kaur, Harpreet; Ray, M. S.; Malhi, S.S.; Thakore, Digpal; Modi, Naresh (International Surgery Journal, 2022)
Background: Anal fissure is a tear in anal canal just below dentate line. It can be acute or chronic. In most patients, it is located in posterior midline. Its treatment is both conservative and surgical. In conservative management, there are no clear guidelines and its goal is to break the cycle of anal sphincter spasm allowing improved blood flow to fissured area for healing. Surgery is considered for patients not responding to conservative measures and its gold standard is lateral internal sphincterotomy. Methods: This prospective study was conducted among 60 patients with acute anal fissure. Patients were randomly divided into two study groups based on treatment protocols conservative management and Bilateral LSIAS. Prior informed written consent was obtained. Demographic profile, history, investigations, diagnosis, treatment and follow-up data was recorded and analyzed. Results: Patients with Bilateral LSIAS got pain relief immediately after surgery. 57% patients with conservative management reported head-ache and perianal itching. Over 86% of patients with Bilateral LSIAS got relief from pain and discomfort after treatment; around over 46% patients with conservative approach, had pain and discomfort after 6 weeks of treatment. Conclusions: Results show that Bilateral LSIAS surgery is a better approach than conservative management of anal fissure. Further, the Bilateral LSIAS surgery has maximum chances of early recovery and pain relief and reduced chances of progression to chronic anal fissure. Hence, we can conclude that for anal acute fissure, Bilateral LSIAS surgery procedure is the treatment of choice.